Forest Resources Access Moro-Moro Farmers at Register 45 Lampung - FX Sumarja; Muhammad Akib (Universitas Lampung, 2018)
The main problem of farmers in Indonesia today is the limited availability of agricultural land. The government gives farmers hope for the availability of agricultural land, through various accesses of forest resources. One of them through a partnership with forest managers. This study will examine the model of forest resource access arrangements and their implementation in Register 45 Sungai Buaya Lampung by Moro-Moro farmers. This study uses a socio-legal approach. This approach combines the study of doctrinal law with social studies. Data required primary data and secondary data. So the analysis is not only based on normative rules but also pay attention to social context.This research shows that forest resource access management model registers 45 Lampung to Moro-Moro farmers is a partnership model. Partnerships offered by forest managers have not provided welfare security to farmers. Forest managers have unilaterally determined types of crops and production sharing balances. The partnership process closes dialogue with farmers. The implementation of this partnership has not been implemented, as most Moro-Moro farmers reject the partnership model offered by forest managers.Keywords: Forest Resources Access, Farmers, Moro-Moro.